Craters in the Telsen area, Chubut Province, Argentina: Satellite imagery digital processing techniques applied to surficial geology mapping - Navarro, Edgardo (2017)
Subcircular features, with crater morphology, developed in a volcano-sedimentary context, with diameters no greater than 2 km, were recognized in the vicinity of the Telsen locality, northeastern Chubut Province, Argentina. These structures are surrounded by tabular volcanic rocks of the Quiñelaf Formation with low radial-centrifugal dip, exhibit an external ring with dark visual levels enclosing topographic highs with mostly light visual levels. Surficial geological aspects of one of the larger structures in the area (S 42° 22´ 55´´, W 66° 49´ 15´´) were mapped from raster data at a scale of 1:3.000, following the stages of the photographic interpretation: Photo-identification, photo-analysis, and photo-intepretation. Panchromatic and multispectral Spot 6 images with 1.5 m and 6 m spatial resolution, respectively were used (Date July 10th 2015); orthorectified with WGS84/UTM and Google Earth image with 0.5 m.spatial resolution. Idrisi Selva, Global Mapper 15, StitchMaps and Corel Draw 17 software were used in the digital processing. The geological references of the area were obtained from the Telsen Geological map, herein georeferenced with Global Mapper. The frequency distribution histograms of the image windows of the different mapped sectors, allowed the generation of different contrast enhancements. Directional filters of the menu texture analysis of Idrisi permitted the identification of the oriented features. The images obtained herein, allowed the recognition of homogeneous units in terms of interpretation keys linked to the photo-analysis phase. Subsequent field observations contributed to the adjustment and to the final assignment of categories to each homogeneous unit (photo-interpretation stage).The final map was compiled with the software Corel Draw, it was based on the synthesis image from the digital processing and referenced using Global Mapper. Deposits and fragments of basalt that constitutes the external ring of the crater along with different volcanic rocks, breccia and Chubut Group rocks fragments enclosed within the crater are mainly showed in this map. Also, deposits and dipping strata of the Chubut Group following the strike of the ring and outcrops of volcanic rocks in the central - south part of the mapped area were recognized. Detailed geophysical surveys detected magnetic anomalies in the SE part of the mapped crater. Several mechanisms such as magmatism, phreatomagmatism and/or bolide impacts constitute hypotheses related to the probable origin of these landforms.